1998
DOI: 10.1200/jco.1998.16.11.3542
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland protection by amifostine in high-dose radioiodine treatment: results of a double-blind placebo-controlled study.

Abstract: Parenchymal damage in salivary glands caused by HD-RIT can significantly be reduced by amifostine, which may improve the quality of life of patients with differentiated thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
61
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 23 publications
1
61
0
Order By: Relevance
“…These trials have shown that amifostine protects against the cytotoxic effects of cisplatin, cyclophosphamide, and radiation therapy. In addition, amifostine protects against xerostomia in patients with head and neck cancer treated with radiation therapy and in patients with thyroid cancer treated with high-dose radio-iodine (Bohuslavizki et al, 1998;Buntzel et al, 1998). Recent observations also indicate that amifostine improves cytopenia in patients with myelodysplastic syndromes (List et al, , 1998.…”
mentioning
confidence: 99%
“…These trials have shown that amifostine protects against the cytotoxic effects of cisplatin, cyclophosphamide, and radiation therapy. In addition, amifostine protects against xerostomia in patients with head and neck cancer treated with radiation therapy and in patients with thyroid cancer treated with high-dose radio-iodine (Bohuslavizki et al, 1998;Buntzel et al, 1998). Recent observations also indicate that amifostine improves cytopenia in patients with myelodysplastic syndromes (List et al, , 1998.…”
mentioning
confidence: 99%
“…Reducing the salivary gland dose will be crucial to reduce the rates of these events. The value of increasing salivation by sour juice and lemon candy remains elusive (8,10), whereas amifostine reduces salivary gland impairment in high-dose radioiodine treatment (10). Our results on the long-term consequences highlight the need to reduce initial salivary gland impairment.…”
Section: Discussionmentioning
confidence: 62%
“…Salivary glands are highly radiosensitive (5) and, accordingly, sialadenitis and xerostomia are the most frequent adverse events of high-dose radioiodine therapy (6). The incidence of sialadenitis after high-dose radioiodine therapy is about 30% (7)(8)(9), and consequent reduced salivary gland function (10) and altered saliva composition (11) develop in all patients. Clinically relevant xerostomia with dry mouth, taste loss, and swallowing difficulties arises in 11%-44% (7)(8)(9).…”
mentioning
confidence: 99%
“…[20][21][22] This cytoprotection has been shown to be mostly effective on normal cells without any interaction with the tumour cells and the anticancer treatment. 16,[23][24][25][26] The present study aimed to evaluate the effect of amifostine on the acute and late side effects of RT, and its tolerability in patients receiving RT for the treatment of head and neck cancer.…”
mentioning
confidence: 99%
“…Preclinical studies reported that while amifostine (Ethyol ® ) decreased the level of damage to the parotid gland due to its cytoprotective property, it also protected normal tissues other than the parotid gland against the side effects of RT and chemotherapy (CT). [11][12][13][14][15][16][17][18] Amifostine is a phosphorylated aminothiol (WR2721) prodrug that preferentially accumulates in the salivary gland where it is metabolized to its active form by alkaline phosphatase, WR1065. 19 This active metabolite acts as a free radical scavenger and is considered the effective cytoprotector against side effects of both CT and RT.…”
mentioning
confidence: 99%